High Mobility 2D Palladium Diselenide Field-Effect Transistors with Tunable Ambipolar Characteristics - Chow, Wai Leong (2017)
Due to the intriguing optical and electronic properties, 2D materials have attracted a lot of interest for the electronic and optoelectronic applications. Identifying new promising 2D materials will be rewarding toward the development of next generation 2D electronics. Here, palladium diselenide (PdSe2), a noble-transition metal dichalcogenide (TMDC), is introduced as a promising high mobility 2D material into the fast growing 2D community. Field-effect transistors (FETs) based on ultrathin PdSe2 show intrinsic ambipolar characteristic. The polarity of the FET can be tuned. After vacuum annealing, the authors find PdSe2 to exhibit electron-dominated transport with high mobility (µe (max) = 216 cm2 V−1 s−1) and on/off ratio up to 103. Hole-dominated-transport PdSe2 can be obtained by molecular doping using F4-TCNQ. This pioneer work on PdSe2 will spark interests in the less explored regime of noble-TMDCs.